Feng Shui in the Land of Monsoon - Nur Aifiah Binti Ibrahim (Britain International for Academic Research (BIAR) Publisher, 2025)
The memories of Han Tzu have left them in awe-inspiring stories to follow. The practicality and spirituality growth among the Feng Shui ancestral sites to visit them back into a deep space. The ergonomics and lifting of the foot have another meaning for the posture of a Buddhist smiling upon the pinnacle of hilltops. The shrine has now been used in words to spread the Feng Shui spirit into their holy land. The secrecy holds other unfolded stories to be inspired among the local celebrities. As the tyrants and other hierarchical officials turn over for their roles and responsibilities in a heavy-duty role. The UNESCO of heritage has now named China one of the tourist attractions in the land called Mushu for the heavenly spirits to divine in such a way that existentialism has another way of naming the cosmo display. The intergalactic for the approach to be on land and not into a deeper space where living things are still trying to find the latest answer of prediction in the gain.